2018
DOI: 10.1186/s12864-018-4691-0
|View full text |Cite
|
Sign up to set email alerts
|

Homoeolog expression bias in allopolyploid oleaginous marine diatom Fistulifera solaris

Abstract: BackgroundAllopolyploidy is a genomic structure wherein two or more sets of chromosomes derived from divergent parental species coexist within an organism. It is a prevalent genomic configuration in plants, as an important source of genetic variation, and also frequently confers environmental adaptability and increased crop productivity. We previously reported the oleaginous marine diatom Fistulifera solaris JPCC DA0580 to be a promising host for biofuel production and that its genome is allopolyploid, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 78 publications
(108 reference statements)
1
19
0
Order By: Relevance
“…The possibility that aASE could be involved in adaptation still faces the question of the clonal heterogeneity of this cellular response (being epigenetic or genetic by nature). This was not ruled out by the studies reported in either F. cylindrus 27 or F. solaris 28 . We thus strongly suggest that any experiments evaluating the impact of aASE upon changing environments in diatoms should be interpreted with care in several sub-populations of clonally isolated cells for genes with AEB > 60%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The possibility that aASE could be involved in adaptation still faces the question of the clonal heterogeneity of this cellular response (being epigenetic or genetic by nature). This was not ruled out by the studies reported in either F. cylindrus 27 or F. solaris 28 . We thus strongly suggest that any experiments evaluating the impact of aASE upon changing environments in diatoms should be interpreted with care in several sub-populations of clonally isolated cells for genes with AEB > 60%.…”
Section: Discussionmentioning
confidence: 93%
“…Around 66% of these genes showed allelic imbalance in at least one experiment, strongly suggesting that allelic imbalance results from species adaptation to new environments. In diatoms, homoeologous gene expression bias (HEB) was furthermore described in the allodiploid and highly oleaginous diatom Fistulifera solaris 28 . In this naturally occurring hybrid species, HEB is widespread with 61% of homoeologous genes showing differential expression (expressed allele ratios > 2).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the allelic imbalance of a synthetic hexaploid wheat showed that 24.1% of the identified homeologous genes were imbalanced in the hybrid, and this difference in expression could not be attributed to preexisting expression divergence between the parentals (Li et al, 2014). Finally, a recent study on the diatom microalgae Fistulifera solaris showed that ∼61% of homeologous genes displayed allelic imbalance (Nomaguchi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Homoeolog expression bias is unequal expression among the homoeologs at different tissues or developmental stages; or as anomaly of their expression level relative to their diploid progenitors 47,49 . Subgenomic preferences have been reported in octoploid strawberry with a single subgenome exhibited significant dominance in gene expression and control of certain metabolomic and disease resistance traits 50 . Contribution of homoeolog expression dominance in facilitating selection of glucosinolate and lipid metabolism genes was also reported in the vegetable-use and oil-use sub-varieties of Brassica juncea 51 .…”
mentioning
confidence: 99%